Akselerasi Peningkatan Kualitas Pendidikan Daerah Tertinggal Melalui Model Pembelajaran Higher Order Thinking Skill (HOTS) di Era Industri 4.0 (Studi Kasus Implemetasi Pilot Project di Kabupaten Halmahera Barat) - Evy Khuriyana; Priyono Priyono (Perwakilan BKKBN Daerah Istimewa Yogyakarta, 2020)
Educational equality is one of the main problems of education in disadvantaged areas. Not only related to accessibility and lack of facilities and infrastructure, but the availability of teaching staff and the quality of teaching and learning also need attention. The government through the Ministry of Villages, Development of Disadvantaged Regions and Transmigration initiated an acceleration of the improvement of the quality of education at the junior secondary level of disadvantaged regions. The pioneering learning model oriented to Higher Order Thinking Skill (HOTS) was conducted with partners who had developed learning using digital learning materials. Submission of subject matter can be online and offline, easily adapted to rural conditions that are difficult to access internet facilities. The implementation of the pilot project in the district which is still in a disadvantaged area, West Halmahera, involves 2 groups of IX A and IX B class students, SMPN 7 West Halmahera. The method used in this study is a quantitative experiment that is by looking at student learning outcomes measured from pre-test and post-test scores conducted on the experimental class and data analysis is done by paired T-test. The results of the study showed that there was a significant increase in student learning outcomes (t hitung > t table). The implementation of HOTS-based learning methods with digital learning material facilities can be replicated for disadvantaged and remote areas that are still lacking the availability of teachers and as a form of anticipation of the preparation of human resources in the Industrial 4.0 era